Pengaruh Sistem Manajemen Kinerja Terhadap Produktivitas Karyawan Di PT Lautan Teduh Interniaga Yamaha Kedaton Bandar Lampung - Ida Syafakoh; Muhammad Yusuf Sulfarano Barusman (Economics and Digital Business Review, 2024)
The influence of management system performance on employee productivity at PT Lautan Teduh Interniaga. The data collection method used was a questionnaire with a Likert scale format, consisting of open and closed questions. This questionnaire was prepared and distributed to 30 respondents to obtain the required responses. A performance management system is defined as a continuous process for recognizing, measuring and improving individual and team performance, and aligning it with organizational goals. The results of the partial hypothesis test show that the management system performance variable (X) has a significant effect on employee productivity, with tcount of 2.991 and ttable of 2.048 at a significance level of 0.006 (smaller than 0.05). Therefore, H0 is rejected and H1 is accepted. The findings of this research show that the performance of the management system has a positive influence on employee productivity by 21.5%, while the remaining 78.5% is influenced by other variables not examined in this study. This research concludes that the performance of the management system plays an important role in increasing employee productivity in the company